Efficacy of Catheter Ablation in Nonparoxysmal Atrial Fibrillation Patients with Severe Enlarged Left Atrium and Its Impact on Left Atrial Structural Remodeling. (10th September 2013) - PUMP, AGNES; DI BIASE, LUIGI; PRICE, JUSTIN; MOHANTY, PRASANT; BAI, RONG; SANTANGELI, PASQUALE; MOHANTY, SANGHAMITRA; TRIVEDI, CHINTAN; YAN, RACHEL (XUE); HORTON, RODNEY; SANCHEZ, JAVIER E.; ZAGRODZKY, JASON; et al.
AF Ablation in Patients with Large LA: Introduction: The effect of catheter ablation on severe left atrial enlargement especially in nonparoxysmal atrial fibrillation (NPAF) patients is not well understood. Whether reverse remodelling may occur after ablation has not been evaluated in this setting. Methods and results: Fifty consecutive patients with left atrial diameter (LAD) ≥50 mm, and LA volume >200 cc undergoing catheter ablation for drug‐refractory NPAF were included in this study. Transthoracic echocardiographic measurements were performed at baseline and at 12‐months postprocedure. Left ventricular end‐diastolic and end‐systolic dimensions were indexed by body surface area (LVEDDI, LVESDI). Electroanatomic mapping system (Carto or NavX system) and computed tomography (CT) were used for 3‐dimensional reconstruction of the LA. All patients underwent posterior wall isolation and pulmonary vein (PV) antrum and extra PV trigger ablations. Long‐term follow‐up was monitored by event recordings, 7‐day Holter monitors and office visits. The mean age was 65 ± 10 years, 78% male, persistent AF 22 (44%), longstanding AF 28 (56%), LAD diameter 56.9 ± 7.8 mm, left ventricular ejection fraction (LVEF) 53 ± 14 and median AF duration 72 (49–96) months. At 12‐month follow‐up, 27 patients (54%) remained arrhythmia‐free off antiarrhythmic drugs. Significant reduction in LAD at follow‐up (≥10% reduction) was observed in 52% (26/50) of the total population and among the 63% (17/27) of recurrence‐free patients. Magnitude of LA reduction was identically distributed among the persistent and longstanding persistent AF cohorts (16 ± 12% vs 14 ± 16%, respectively, P = 0.15). A significant 20% improvement in LVEF (from 53 ± 14 to 58 ± 9, P = 0.03) was found in the overall population. Improvement was noted in recurrence‐free patients. No significant change in LVEDDI and LVESDI was noted. After adjusting for baseline risk factors in a multivariable model, a reduction in LAD was identified as a strong predictor of long‐term success (beta = –11.1, P = 0.013). Preexisting LA scarring was associated with increased LAD (beta = 2.7, P = 0.023). No periprocedural or long‐term complications were reported. Conclusion: Our results show that atrial fibrillation ablation is effective in NPAF patients with severe LA enlargement and is associated with LA reverse remodeling and improvement in LVEF.